Metode Agile untuk Digitalisasi Sistem Pemesanan Layanan Berbasis Mobile dengan Fitur Konsultasi dan Pembayaran Online - Pandji Hatma Syahdinata; Adam Sekti Aji (Bulletin of Computer Science Research, 2025)
The development of information technology has driven transformation in the service and trade sectors, including the online management of product and service orders. The ordering system at PT. Cahaya Gemilang Engineering (CGE) is inefficient and often experiences a backlog of purchase orders. This has become a major problem and has had an impact on sales. The development of a web-based and mobile service ordering system aims to make it easier for customers to place technical service orders more flexibly. Research has also been conducted on the digitization of the system. This has become a major problem and has impacted sales. The development of a web-based and mobile service ordering system aims to make it easier for customers to place technical service orders and be more flexible. Research has also been conducted on system digitization by integrating various key features, such as product and service management, order management, online consultation via chat, automatic payment systems, expense management, and financial reporting. This feature can overcome shopping queue backlogs and make the payment process more organized and efficient. The system flow was designed using Unified Modeling Language (UML) such as use case diagrams, activity diagrams, and sequence diagrams. The system was developed using the Laravel framework for the web platform and Flutter for the mobile application. The method used was the Agile Development approach. The black box method was also used to test the system. The test results showed that the system was able to provide efficiency in managing company services, improve the ease of interaction between customers and administrators, and produce accurate financial reports.